2020
DOI: 10.3389/fpubh.2020.00482
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Preparedness of COVID-19 Outbreak Among Healthcare Workers and Other Residents of South-West Saudi Arabia: A Cross-Sectional Survey

Abstract: Background: Coronavirus disease-2019 (COVID-19) was declared a "pandemic" by the World Health Organization (WHO) in early March 2020. Globally, extraordinary measures are being adopted to combat the formidable spread of the ongoing outbreak. Under such conditions, people's adherence to preventive measures is greatly affected by their awareness of the disease. Aim: This study was aimed to assess the level of awareness and preparedness to fight against COVID-19 among the healthcare workers (HCWs) and other resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
76
3
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 27 publications
15
76
3
4
Order By: Relevance
“…So, a previous study as well as this study strongly suggested that washing the hands regularly and maintaining social distancing are the most significant factors for reducing the spread of coronavirus. We also compared this study with another that was conducted in a rural area of Saudi Arabia ( Tripathi et al., 2020 ) and our results are in line with those reported for the rural population in Saudi Arabia.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…So, a previous study as well as this study strongly suggested that washing the hands regularly and maintaining social distancing are the most significant factors for reducing the spread of coronavirus. We also compared this study with another that was conducted in a rural area of Saudi Arabia ( Tripathi et al., 2020 ) and our results are in line with those reported for the rural population in Saudi Arabia.…”
Section: Discussionsupporting
confidence: 86%
“…We have compared the results from this study with the existing works of literature, and our research found similar conclusions as previous research ( Deblina et al, 2020 ) involving the knowledge about social distancing as a significant factor. A recent cross-sectional ( Tripathi et al., 2020 ) was conducted in the South-west of Saudi Arabia to assess the awareness among social workers and the study emerged social distancing and hand hygiene as significant factors for awareness like this research. So, a previous study as well as this study strongly suggested that washing the hands regularly and maintaining social distancing are the most significant factors for reducing the spread of coronavirus.…”
Section: Discussionmentioning
confidence: 97%
“…The subset of participants with a higher perception of risk was found to be more likely to adopt NPIs in both. Interestingly, several surveys confirm the expectation coming from the health belief model pointing to the fact that knowledge about the disease and perceived risks are predictors behavioral changes [198] , [204] , [206] , [208] , [214] , [215] , [216] . The adoption of face masks has been found to be negatively affected by perception of shortage in New Zealand [206] , and positively influenced by national guidelines in the USA [211] .…”
Section: Surveysmentioning
confidence: 74%
“…The finding of this study is supported by a study conducted in Riyadh, Saudi Arabia, 26 and South-West Saudi Arabia. 14 This finding gives hint that public health awareness creation campaigns should continue to improve community awareness about the disease. The outcome of this study highlighted a growing need for the adoption of innovative local strategies to improve awareness in the general population related to COVID-19 and its preventative practices in order to meet its elimination goals.…”
Section: Discussionmentioning
confidence: 96%
“…4 However, appropriately implementing public health and social (PHS) measures ranging from individuals to large societal level practices are the only available means to control the spread of the virus and minimize its impacts. 12 , 14 The term “public health measures” refers to means to decrease or interrupt transmission of COVID-19 by practicing hand washing, social distancing, wearing the face mask and stay-at-home lockdown measures were means to prevent and control COVID-19 transmission. 15–21 A study showed non-pharmaceutical interventions like physical distancing measures were effective in the reduction of infections.…”
Section: Introductionmentioning
confidence: 99%